EDUCATION, TECHNOLOGY AND ETHIC - Acevedo Tovar, Luz Marina (2014)
This investigation explores the connection between education, technology and ethics; technology is necessary for the development of our society, however it is not enough to guarantee human development in terms of life quality. Life quality should be understood as full human development in a cultural and social context. The supposed neutrality of science and technology is questionable; as human constructions science and technology are subject to men’s intelligence and will; the use or abuse of them is a human decision. Decisions, behavior and human activity are always moral subjects, especially when they affect other people. Thus, we need to debate and think of this, as well as use an ethical judgment. Technology must be evaluated with ethical criteria or else it could contribute to our society dehumanization. It is precisely in this matter that education intervenes, creating attitudes and setting behaviors. Our proposal is that ethics become the main urge in educative curricula structure.